A multicolour flow cytometric assay for c-MYC protein in B-cell lymphoma. Issue 10 (16th May 2018) - Alayed, Khaled; Schweitzer, Karen; Awadallah, Amad; Shetty, Shashirekha; Turakhia, Samir; Meyerson, Howard
Abstract : Aim: Develop an objective assay to detect c-MYC protein expression using multiparametric flow cytometry (FCM) as an alternative to immunohistochemistry (IHC). Methods: 57 patient samples and 11 cell line samples were evaluated. Cell suspensions were obtained and c-MYC staining was performed in combination with CD45 and CD19 and, in some samples, CD10. The percentage of c-MYC+ cells by FCM was correlated with the percentage determined by IHC. The relationship between c-MYC protein expression and the presence of a c-MYC gene rearrangement in aggressive and high-grade lymphomas was also assessed. Results: c-MYC expression by FCM and IHC demonstrated a high degree of correlation in a training set of 33 patient cases, r=0.92, 11 cell line samples, r=0.81 and in a validation set of 24 aggressive and high-grade B-cell lymphomas, r=0.85. c-MYC gene was rearranged by fluorescence in situ hybridisation in 6/9 samples with high c-MYC expression (>40%) by FCM and 6/14 by IHC. Conclusions: We have developed a reliable multicolour FCM assay to detect c-MYC expression suitable for clinical laboratories that should be helpful to accurately quantify c-MYC expression in B-cell lymphomas.